2015
DOI: 10.5665/sleep.5236
|View full text |Cite
|
Sign up to set email alerts
|

Diet/Energy Balance Affect Sleep and Wakefulness Independent of Body Weight

Abstract: Acute dietary manipulations are sufficient to alter sleep and wakefulness independent of body weight and without effects on sleep homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…A recent study reported that one-week ad libitum feeding with increased calorie density (high fat diet) resulted in increased sleep/wake fragmentation in mice [11], which indicates a link between excessive energy consumption and disturbed sleep. A human study of acute diet alteration in normal sleepers has shown that, compared to limited total energy intake, sleep after ad libitum feeding was characterized by longer SOL and shorter slow wave sleep [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported that one-week ad libitum feeding with increased calorie density (high fat diet) resulted in increased sleep/wake fragmentation in mice [11], which indicates a link between excessive energy consumption and disturbed sleep. A human study of acute diet alteration in normal sleepers has shown that, compared to limited total energy intake, sleep after ad libitum feeding was characterized by longer SOL and shorter slow wave sleep [10].…”
Section: Discussionmentioning
confidence: 99%
“…Diet is an important mediator between sleep and overweight/obesity. Growing evidence suggest that diet alterations can directly influence sleep parameters [10,11]. Furthermore, the associations between nutrients and insomnia symptoms have been reported by recent studies [12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Surgery for EEG/EMG (electromyography) recording and data acquisition and analysis were performed as previously described ( 32 , 33 ). Briefly, EEG/EMG headmounts were manually constructed and implanted onto mice anesthetized with ketamine (100 mg/kg) and xylene (10 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…Sleep recordings were conducted as previously described (Perron, Pack & Veasey, ). Briefly, silver wire electrodes were soldered to gold sockets and push fit into 6‐channel plastic holders.…”
Section: Methodsmentioning
confidence: 99%